Influence of smoking consumption and nicotine dependence degree in cardiac autonomic modulation - dos Santos, Ana Paula Soares [UNESP]; Ramos, Dionei [UNESP]; de oliveira, Gabriela Martins [UNESP]; dos Santos, Ana Alice Soares [UNESP]; Freire, Ana Paula Coelho Figueira [UNESP]; Ito, Juliana Tiyaki; Fernandes, Renato Peretti Prieto; Vanderlei, Luiz Carlos Marques [UNESP]; Ramos, Ercy Mara Cipulo [UNESP] (Sociedade Brasileira de Cardiologia, 2016)
Background: Smoking consumption alters cardiac autonomic function. Objective: Assess the influence of the intensity of smoking and the nicotine dependence degree in cardiac autonomic modulation evaluated through index of heart rate variability (HRV). Methods: 83 smokers, of both genders, between 50 and 70 years of age and with normal lung function were divided according to the intensity of smoking consumption (moderate and severe) and the nicotine dependency degree (mild, moderate and severe). The indexes of HRV were analyzed in rest condition, in linear methods in the time domain (TD), the frequency domain (FD) and through the Poincaré plot. For the comparison of smoking consumption, unpaired t test or Mann-Whitney was employed. For the analysis between the nicotine dependency degrees, we used the One-way ANOVA test, followed by Tukey’s post test or Kruskal-Wallis followed by Dunn’s test. The significance level was p < 0,05. Results: Differences were only found when compared to the different intensities of smoking consumption in the indexes in the FD. LFun (62.89 ± 15.24 vs 75.45 ± 10.28), which corresponds to low frequency spectrum component in normalized units; HFun (37.11 ± 15.24 vs 24.55 ± 10.28), which corresponds to high frequency spectrum component in normalized units and in the LF/HF ratio (2.21 ± 1.47 vs 4.07 ± 2.94). However, in the evaluation of nicotine dependency, significant differences were not observed (p > 0.05). Conclusion: Only the intensity of smoking consumption had an influence over the cardiac autonomic modulation of the assessed tobacco smokers. Tobacco smokers with severe intensity of smoking consumption presented a lower autonomic modulation than those with moderate intensity.
Keywords: Smoking; Tobacco use / complications; Tobacco use disorders